Nocturna a live-in BPO Complex facilitating the improvement of sleep patterns and lifestyle for night shift workders - Espino, Guillermo Antonio B.; Navarra, Nappy L. (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
In recent years, the Business Process Outsourcing Industry (BPO) has flourished in the Philippine market, creating thousands of job opportunities for the local workforce and contributing greatly to the country's economic growth. However, the industry which calls for its employees to work shifts typically from midnight to early morning has left these people with no soultion to the poor sleeping habits, health problems and impaired mental capacities that are caused by their line of work. More so, there is a lack of structures or systems designed to help night shift workers improve their lifestyles, as majority of local parks are designed for day use an even less are designed to help people with poor sleeping habits. The design proposal of "Nocturna: A Live-in BPO Complex Facilitating the Improvement of Sleep Patterns and Lifestyle for Night Shift Wokers" aims to help night shift workers to improve their sleeping habits and lifestyle with landscape architecture. The live-in BPO complex located on site of Convergys Nuvali, Sta. Rosa is a controlled environment that includes a sleeping quarters, winding down area, exercise area and socials area, all of which will be used according to the directive of prepared programs.
Includes appendices
Thesis (Bachelor of Landscape Architecture)--University of the Philippines Diliman
Keywords: Architecture -- Human factors; Buildings -- Landscape architecture